ZRSR1 co-operates with ZRSR2 in regulating splicing of U12-type introns in murine hematopoietic cells - Madan, Vikas (2022)
Recurrent loss-of-function mutations of spliceosome gene, ZRSR2, occur in myelodysplastic syndromes (MDS). Mutation/loss of ZRSR2 in human myeloid cells primarily causes impaired splicing of the U12-type introns. In order to further investigate the role of this splice factor in RNA splicing and hematopoietic development, we generated mice lacking ZRSR2. Unexpectedly, Zrsr2-deficient mice developed normal hematopoiesis with no abnormalities in myeloid differentiation evident in either young or ≥1-year old knockout mice. Repopulation ability of Zrsr2-deficient hematopoietic stem cells was also unaffected in both competitive and non-competitive reconstitution assays. Myeloid progenitors lacking ZRSR2 exhibited mis-splicing of U12-type introns, however, this phenotype was moderate compared to the ZRSR2-deficient human cells. Our investigations revealed that a closely related homolog, Zrsr1, expressed in the murine hematopoietic cells, but not in human cells contributes to splicing of U12-type introns. Depletion of Zrsr1 in Zrsr2 KO myeloid cells exacerbated retention of the U12-type introns, thus highlighting a collective role of ZRSR1 and ZRSR2 in murine U12-spliceosome. We also demonstrate that aberrant retention of U12-type introns of MAPK9 and MAPK14 leads to their reduced protein expression. Overall, our findings highlight that both ZRSR1 and ZRSR2 are functional components of the murine U12-spliceosome, and depletion of both proteins is required to accurately model ZRSR2-mutant MDS in mice.